HOUSEHOLD AGE STRUCTURE AND CONSUMPTION IN SERBIA - Radivojević, Biljana; Vasić, Petar (Economic Annals, 2012)
The influence of demographic variables on household consumption level and structure is understood but insufficiently studied in Serbia. This paper analyzes the connection between age as a demographic variable, and the size and structure of household consumption as economic phenomena. We discuss the research results, trying to explain the intensity and direction of the shown connection. The economic variables are usually set as determinants of demographic processes, but we set age as an independent demographic variable shaping household consumption without ignoring the household income level. It seems that the age structure of a household, particularly the age of the household head, has a significant influence on consumption structure.